he effect of infrastructure on economic growth in Indonesia - Tunjung Hapsari (Journal on Economics, Management and Business Technology, 2022)
Infrastructure development of infrastructure in Indonesia has been going on for quite a long time and the investment incurred is very big. But still quite a lot of problems experienced by our country in particular regarding the weak planning, insufficient quantity, poor quality, and so forth. The problems discussed in this study is whether the factors of production are represented by the infrastructure (roads, electricity, telephone, and water) have a significant influence and contribution to the output variables are represented by per capita income for the government to set policy direction in the development of infrastructure in Indonesia. The data used are panel data with the period from 2004 to 2009 for 26 provinces in Indonesia. To find the results of the BLUE (Best Linear Unbiased Estimator), the test for a panel like the Chow Test and Hausman Test so that got fixed effect panel data model for the complete data with characteristics as above. Then do the test assumptions such as Classical multicollinearity, Heteroskidastity, and autocorrelation. The end result is the four independent variables above, which have two variables that have a significant effect on economic growth of the road, electricity and two more variables which have no significant effect of telephone and water.